The Influence Of Music On Memorization Performance Of Mathematics Students - Yuhaniz Ahmad; Fatinah Zainon; Zaliza Ghazali; Noraziah Man; Fathilah Mohd Alipiah; Muhammad Yasir Mohamad Yunus (Proceedings of The ICECRS, 2017)
Science has indicated that the left side of the brain performs tasks that are related to logic, such as in science and mathematics while the right performs tasks related to creativity and arts, including music which can affects the brain in many positive ways. Mathematics students tend to use the left brain more than the right brain and as a result, they may encounter difficulties in courses that are not related to mathematics which require reading and memorizing. Learning process and retention of information can be maximized with the simultaneous left and right brain activation. Music is believed to induce better memorization performance Therefore, in this study we introduce music during the memorization process to enhance the use of the right brain. A Complete Randomized Block Design experiment that has been done on mathematics students for testing the effect of music on memorizing performance shows that listening to music during memorizing improve the memorization performance. Furthermore, there is a difference in effectiveness in memorization performance using different types of music. Classical music has been found to be the best music to improve memorization performance. In conclusion, music can be considered as a tool by educators, parents and students to improve learning process.